Investigations on Strong-Tuned Magnetocaloric Effect in La0.5Ca0.1Ag0.4MnO3 - Hamad, Mahmoud A.; Alamri, Hatem R. (Frontiers in Materials, 2022)
The magnetocaloric effect (MCE) of La0.5Ca0.1Ag0.4MnO3 (LCAMO) is simulated using a phenomenological model (PM). LCAMO MCE parameters are calculated as the results of simulations for magnetization vs. temperature at different values of the external magnetic field (Hext). MCE's temperature range in LCAMO grew as the variation in Hext increased, eventually covering room temperature at high Hext values. MCE of LCAMO is tunable with the variation of Hext, approving that LCAMO gives practically more helpful as a magnetocaloric (MC) material for the development of MRs in an extensive temperature range, including room temperature, low and higher ones. MCE parameters of LCAMO are practically more MCE ones of some MC samples in earlier works.